AUXIN-PRODUCING PLANT GROWTH-PROMOTING RHIZOBACTERIA PROMOTE ROOT FORMATION OF EPIPREMNUM AUREUM CUTTINGS - H. C. Kaymak1; M. A. Irmak; A. Aksoy; N. Tekiner (Journal of Animal and Plant Sciences, 2021)
This work was conducted to determine the possible influences of auxin-producing plant growth promoting rhizobacteria (PGPR) on root formation of Epipremnum aureum stem cuttings for environment friendly commercial production. Agrobacterium rubi A-16, Bacillus megaterium M-3, TV-91C and TV-6D were used to increase rooting performance. The new root formation was higher (51.67-75.00%) in all bacteria strain treatments as compared to control (36.67%). Root and shoot length were longer in cuttings inoculated with Agrobacterium rubi A-16 compared with other bacteria strains. The root and shoot lengths were lower than bacteria treatments in control cuttings. The dry matter content of roots varied from 7.27% (M-3) to 8.33% (A-16). The highest new leaf number (2.97) was counted in TV-6D followed by 2.87 in treatment TV-91C. The leaf area and chlorophyll content varied from 8.41 cm2 (control) to 10.32 cm2 (M-3) and 22.60 (TV-6D) to 25.97 (TV-91C), respectively. The mean values of examined properties of Epipremnum aureum cuttings treated with auxin-producing plant growth promoting rhizobacteria were better than control. Plus, when bacteria strains were evaluated among themselves, it could be said that the effect of Agrobacterium rubi A-16 on the examined parameters were higher than other bacteria strains and can be suggested for producers of Epipremnum aureum and other ornamental species for vegetative propagation.
Keywords: Agrobacterium rubi; Bacillus megaterium; ornamental plants; propagation